Digestion of sweet potato foliage (Ipomoea batatas (L.) Lam) in pigs. Ileal and rectal digestibility of nutrients and energy - D?az, Ivonne; Gonz?lez, C.; Reyes, J. L.; Ly, Julio (Cuban Journal of Agricultural Science, 2014)
Two experiments were performed, according to Latin square 4x4, to determine the ileal and rectal digestibility of nutrients and energy in growing Yorkshire x Landrace pigs. They were fed with variable levels (0, 10, 20 and 30 % on dry basis) of sweet potato foliage meal (Ipomoea batatas (L.) Lam). In experiment 1, four castrated males, of 35 kg and prepared with an ileo-rectal anastomosis, were used. In experiment 2, eight non castrated pigs of 38 kg were used. It was confirmed that the ileal digestibility of DM, organic matter and energy decreased significantly (P < 0.05) with the inclusion of the foliage. However, there were no differences between the treatments with 0 and 10 % of the foliage, nor with 10 and 30 %. The rectal digestibility showed the same fact (P < 0.05) for the DM, organic matter and energy. The ileal and rectal digestibility, measured by difference, were 34.4 and 61.1% for the organic matter of the foliage, and 40.6 and 59.0 % for the energy. From the digestive point of view, the sweet potato foliage meal can be provided to pigs in levels not higher than 30 % of the food, as a source of proteins and minerals in diets of very low amount of fiber. Key words: pigs, digestion, ileum, nutrients, sweet potato foliage